Inovasi Media Pembelajaran Berbasis Karakter di TPQ Nurul Ilmiyah Desa Kudubanjar - Umardiyah, Fitri; Zuhriawan, M. Qoyum; Hasanah, Roisatul; Ilmi, Khusnul Abidah; Prihatiningtyas, Suci (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
TPQ is an informal institution that parents rely on in educating children to learn the Qur'an from an early age. One of the things that is often underestimated in the management of TPQ is the learning process carried out without paying attention to aspects that can affect the character of children's interest and attractiveness to learn and love the Qur'an. Learning that takes place in TPQ seems to use methods, strategies, and learning media that are 'as is' and lack innovation. This problem occurs at TPQ Nurul Ilmiyah. The solution offered is through the innovation of al-Qur'an learning media in the form of Tilawati backsheet props. The implementation of the activity consists of two stages, namely assistance in preparing learning media and implementing media in learning. The results obtained are santri are more enthusiastic in learning because they use interesting media so that it is expected to increase interest and motivation in learning the Qur'an.